(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Indian Railways cross the catering industries and facilities delivered every day to 22 million travelers. Improving catering quality is a phase that is continuing. Indian Railways has established an effective and institutionalized system to track the standard and hygiene of catering facilities by frequent inspections at different levels in its efforts to provide passengers with safe and hygienic food. The degree of customer satisfaction is often tracked routinely by direct and other methods of coping with catering grievances. This experiment is carried out on a group of 80 passengers in selected trains to evaluate catering satisfaction standards for Indian Railways. The respondents were randomly chosen from the community.